A landscape of micronutrient status in women through the reproductive years: Insights from seven regions in Asia - Chong, Mary Foong-Fong (Womens Health (Lond), 2020)
Optimal micronutrient status is critical to the health of women, particularly during their reproductive years. A woman’s health and nutritional status during the preconception stage thus has significant implications for pregnancy outcomes and her offspring’s health later in life. In this review, we evaluated micronutrient intakes and status (iron, folate, and vitamin B12) of women in their reproductive years and during pregnancy, along with associated health consequences and dietary causes, across seven regions in Asia, namely, Hong Kong, Indonesia, the Philippines, Singapore, Taiwan, Thailand, and Vietnam. A structured literature search, targeting peer-reviewed publication databases, as well as data from international and national sources in the public domain, was conducted. Our review of the nutritional landscape demonstrates that micronutrient deficiency–related conditions, especially anemia and its associated health consequences, are common among Asian women of reproductive age, yet the dietary causes are poorly studied. Inadequate or borderline dietary intake of micronutrients and low consumption of micronutrient supplements were evident, despite existing recommendations, food fortification, and supplementation strategies. Evaluation of current programs through nutrition monitoring and improvement of supplementation strategies, such as supplementing with multiple micronutrients, alongside food-based programs, will help better support the health of women through their reproductive years.